2003
DOI: 10.1099/mic.0.26157-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in GE2270 antibiotic production in Planobispora rosea through modulation of methylation metabolism

Abstract: Thiazolylpeptide GE2270 is a potent antibiotic inhibiting protein synthesis in Gram-positive bacteria. It is produced as a complex of 10 related metabolites, differing mainly in the degree of methylation, by fermentation of the rare actinomycete Planobispora rosea ATCC 53773. Addition of vitamin B12 to the fermentation medium doubled total complex production and markedly changed the relative production of the various GE2270 metabolites, enhancing the biosynthesis of the more methylated component A. Among methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…As previously reported, the addition of Vitamin B12 to the fermentation medium directed GE2270 complex production toward the selective synthesis of factor A [5]. Thus, data herein reported refer to GE2270 factor A production.…”
Section: Liquid Media Fermentationsupporting
confidence: 58%
See 3 more Smart Citations
“…As previously reported, the addition of Vitamin B12 to the fermentation medium directed GE2270 complex production toward the selective synthesis of factor A [5]. Thus, data herein reported refer to GE2270 factor A production.…”
Section: Liquid Media Fermentationsupporting
confidence: 58%
“…P. rosea PR1/5 was isolated by N-methyl-N¢-nitro-Nnitrosoguanidine (MNNG) (Fluka, Buchs, Switzerland) treatment from the natural variant PR9/1 [5]. Spontaneous resistant mutants of strain PR1/5 (and selected derivatives) arose with frequencies between 10 À7 -10 À9 and were selected by spreading sonicated hyphae, prepared according to Beltrametti et al [2], on plates supplemented with 200 mg/l streptomycin (Sigma-Aldrich, St. Louis, MO, USA), 100 mg/l rifamycin (Sigma-Aldrich) or 1 mg/l gentamycin (Sigma-Aldrich).…”
Section: Strains and Cultural Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Numerous reports on the increase in production of methylated antibiotics and the decrease in production of demethylated antibiotics by the addition of cobalt or vitamin B 12 to fermentation have been reported. [10][11][12][13] All the above methylated antibiotics require methionine as methyl donor. Using [13C-methyl]-methionine in a feeding study experiment, we found that the methyl group of methionine did not incorporate into NPI-0047 and NPI-0052 (data not shown).…”
Section: Culturing Conditions Extraction and Hplc Analysismentioning
confidence: 99%